Social capital and social media factors of sustainable indigenous tourism of the Mah Meri in Carey Island, Malaysia - Abd Hamid, Zuliah (2022)
The main purpose of this study is to understand the influencing factors of sustainable indigenous tourism holistically. Specifically this study aims to examine the influence of community source, social capital and social media on sustainable indigenous tourism of the Mah Meri, in Carey Island, Malaysia. This research contributes to the scope of indigenous tourism and social media. Mah Meri indigenous people of Carey Island, Selangor, were selected due to their strong participation in tourism. Kampung Sungai Bumbon is also declared as a Cultural Village by the government to promote indigenous activities there. This study employs a quantitative approach that forms the use of social media in indigenous tourism development. Apart from social media, this study also employs social capital theory, especially bridging, bonding, and linking. The gap in Social Capital Theory is addressed in relation to social media utilization towards sustainable tourism. The quantitative approach is used in this study to gather and analyze data. Several statistical analyses of SPSS were applied in this study to examine the data and hypotheses testing. Finally, Structural Equation Modelling (SEM)- PLS (Partial Least Squares) analysis was executed to evaluate exogenous and endogenous constructs' relation. Results found that the empirical analysis of the direct effects of sustainable indigenous tourism is the research's main theoretical contribution, especially to tourism literature. First, the community sources (including culture, nature and knowledge) and social media (adaption, participation, interactivity and sharing) significantly influenced sustainable indigenous tourism. Secondly, the outcomes revealed that social capital did not influence sustainable indigenous tourism, although past literature demonstrated a significant relationship between these variables. Thirdly, the study also presented an extended research model that combined community sources, social capital, social media and sustainable tourism that had not been tested together in the previous studies. The outcomes of moderating effects through hierarchical multiple regression analysis indicated that the income and educational level were significantly influenced the relationship between social capital and sustainable indigenous tourism. Most of these constructs were tested either separately or with a combination of two related constructs in the past literature. Thus, the finding of this study added new knowledge to the tourism pieces of literature. Thus, the social capital of the community plays a significant role. It is suggested that the community should be given authority in the decision-making process. Apart from that, they must be empowered and financially supported to run their own tourism business. Therefore, government organizations need to concentrate more on these areas (significant variables) and support the local community to attain a holistic, sustainable tourism practice.